Nestin, CD44, Ki-67, GS and AQP4 expression in the brain neurogenic niches of deceased patients with liver cirrhosis of different degree - Shulyatnikova, T. V.; Tumanskyi, V. O.; Шулятнікова, Тетяна Володимирівна; Туманський, Валерій Олексійович (Запорізький державний медико-фармацевтичний університет, 2023)
The aim of the study. Immunohistochemical study of Nestin, CD44, Ki-67, GS, AQP4 expression in the subventricular zone of the lateral ventricle and hippocampus of deceased patients with liver cirrhosis depending on the age and Child–Pugh score. Materials and methods. The brains of 90 deceased patients aged 65 ± 3 years with non-alcoholic liver cirrhosis (LC) Child–Pugh class A, B and C were studied, which comprised 3 groups: group “A” – 30 deceased patients with compensated LC; “B” – 30 deceased patients with subcompensated LC (“mild decompensation”); “C” – 30 deceased patients with decompensated LC. Control group included brains of 30 patients died from acute cardiovascular failure and did not have liver disease. Each group was divided into 2 subgroups: patients ≤59 y. o. and patients ≥60 y. o. Grade 1–4 hepatic encephalopathy was detected in 59 out of 90 (65.55 %) patients with LC. The immunohistochemical levels of Nestin, CD44, Ki-67, GS and AQP4 were evaluated in paraffin tissue sections of the subventricular zones (SVZ) of the anterior and lower horns of the brain lateral ventricles, as well as the subgranular zone (SGZ) of the dentate gyrus (DG) and other structures of hippocampus in standardized fields of view of the microscope Scope A1 Carl Zeiss (Germany) using Videotest-Morphology 5.2.0.158 software. Results. In SVZ of control subgroups, Nestin+ astrocyte-like stem cells were localized mainly in subventricular glial nodules (SGN) and to a lesser extent in astrocytic ribbon. In brains of patients with compensated and subcompensated LC, there was increased Nestin expression compared to control (by 61.36 % and 208.74 %, respectively) due to increased numbers of Nestin+ cells in astrocytic ribbons. In the hippocampus of control and cirrhotic patients, Nestin expression was determined mainly in astrocyte-like cells of the fimbria-fornix, “glial plates” around the blood vessels entering the choroid plexus and subpial zone. In the SVZ of patients with subcompensated LC, the expressions of Nestin, CD44, and Ki-67 were maximally increased (by 208.74 %, 37.83 %, and 3 times, respectively), moreover, in the areas of periventricular reparative astrogliosis, in small foci of encephalolysis in the head of caudate nucleus, among GS+ and CD44+ astrocytes clusters of astrocyte-like Nestin+ and CD44+ cells were detected. In patients with decompensated LC, a significant decrease in Nestin and CD44 expression and absence of Ki-67 were observed in the SVZ, with a simultaneous maximum increase in the expression of GS and AQP4. Мета роботи – імуногістохімічне дослідження експресії Nestin, CD44, Ki-67, GS, AQP4 у субвентрикулярній зоні бічного шлуночка та гіпокампі померлих хворих на цироз печінки різних вікових груп залежно від стадії захворювання за Чайлд–П’ю. Матеріали та методи. Дослідили головний мозок (ГМ) 90 померлих (вік – 65 ± 3 роки) хворих на неалкогольний цироз печінки (ЦП) класу А, В і С за Чайлд–П’ю. Сформували 3 групи спостережень: група «А» – 30 померлих хворих на компенсований ЦП; «В» – 30 померлих хворих на субкомпенсований ЦП; «С» – 30 померлих хворих на декомпенсований ЦП. У групі контролю – ГМ 30 померлих від гострої серцево-судинної недостатності, які не мали захворювань печінки. Кожну групу поділили на 2 підгрупи за віком: ≤59 років і ≥ 60 років. У 59 із 90 (65,55 %) хворих на ЦП визначили симптоматику печінкової енцефалопатії I–IV ступенів. У парафінових зрізах тканини субвентрикулярних зон (SVZ) переднього та нижнього рогів бічних шлуночків ГМ, а також субгранулярної зони (SGZ) зубчастої звивини (DG) та інших структур гіпокампа визначили рівень імуногістохімічної експресії Nestin, CD44, Ki-67, GS і AQP4 у стандартизованих полях зору мікроскопа Scope A1 Carl Zeiss (Germany) з програмою Відеотест-Морфологія 5.2.0.158. Результати. У SVZ ГМ контрольних підгруп Nestin+ астроцитоподібні стовбурові клітини локалізувалися здебільшого в субвентрикулярних гліальних вузликах (SGN), менше – в астроцитарних стрічках. У ГМ хворих на компенсований і субкомпенсований ЦП встановили підвищену експресію Nestin щодо контролю (на 61,36 % і 208,74 % відповідно) внаслідок підвищення кількості Nestin+ клітин в астроцитарних стрічках. У гіпокампі контрольних пацієнтів і хворих на ЦП експресію Nestin визначали передусім в астроцитоподібних клітинах бахромки-склепіння, «гліальних пластинок» основи судин хоріоїдного сплетення та субпіальної зони. У SVZ ГМ хворих на субкомпенсований ЦП експресія Nestin, CD44 і Ki-67 максимально підвищувалася (на 208,74 %, 37,83 % і втричі відповідно), а в ділянках перивентрикулярного репаративного астрогліозу в дрібних вогнищах енцефалолізису голівки хвостатого ядра серед GS+ і CD44+ астроцитів визначили скупчення астроцитоподібних Nestin+ і CD44+ клітин. У хворих на декомпенсований ЦП у SVZ ГМ спостерігали значне зниження експресії Nestin і CD44, відсутність експресії Ki-67 при одночасному максимальному підвищенні експресії GS і AQP4.
Характеристика експресії Nestin, CD44, Ki-67, GS і AQP4 у стовбурових нейрогенних нішах головного мозку померлих хворих на цироз печінки різних ступенів тяжкості
Shulyatnikova T. V. - ORCID ID: 0000-0002-0196-9935; Tumanskyi V. O. - ORCID ID: 0000-0001-8267-2350.
Keywords: hepatic encephalopathy; neurogenesis; astrocytogenesis; stem cells; Nestin; CD44; Ki-67; GS; AQP4; печінкова енцефалопатія; нейрогенез; астроцитогенез; стовбурові клітини